Gut microbiota dysbiosis in polycystic ovary syndrome: focus on diet, probiotics, and traditional Chinese medicine - Zhu, Shuangquan; Chen, Hao; He, Bing; Zhang, Yi; Li, Ping; Kuang, Jilin (Frontiers in Microbiology, 2025)
Polycystic ovary syndrome (PCOS) is a complex endocrine and metabolic disorder, primarily characterized by symptoms such as ovulatory dysfunction, hyperandrogenism, and polycystic ovarian morphology. In recent years, research has revealed that gut microbiota dysbiosis plays a crucial role in the pathogenesis of PCOS. Diet, as an essential factor in regulating gut microbiota, significantly impacts the clinical presentation and metabolic status of PCOS patients. Although substantial research has explored the relationship between PCOS and gut microbiota, many controversies and gaps remain, including the unclear mechanisms by which dietary structure and nutritional interventions specifically influence PCOS. This review aims to summarize the interaction between PCOS and gut microbiota, explore the role of diet in modulating gut microbiota and improving the pathological state of PCOS, and evaluate the potential therapeutic effects of probiotics, high-fat diets, and ketogenic diets on PCOS. Ultimately, it looks forward to personalized nutritional treatment strategies based on gut microbiota and future research directions, providing new insights into the treatment of PCOS.